2020
DOI: 10.3390/brainsci10010049
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy Is Associated with Lower Memory Function in African American Older Adults

Abstract: Although previous research has linked polypharmacy to lower cognitive function in the general population, we know little about this association among economically challenged African American (AA) older adults. This study explored the link between polypharmacy and memory function among AA older adults. This community-based study recruited 399 AA older adults who were 65+ years old and living in economically disadvantaged areas of South Los Angeles. Polypharmacy (taking 5+ medications) was the independent variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
3
6
2
Order By: Relevance
“…Our study shows that similar to findings by Bailey et al from a nine year follow-up, patients with multiple co-morbidities were at the greatest risk as well as frequently having complex medication regimens [25] with subsequent negative health outcomes [26]. In another study conducted among 200 community-dwelling seniors, almost half of the participants had medication regimens that were complex; the common causes identified included misunderstanding of medication instructions and polypharmacy [27]. Polypharmacy has worsened over the last three decades with prescribed medication usage doubling to four times from 1988 to 2010 [28].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our study shows that similar to findings by Bailey et al from a nine year follow-up, patients with multiple co-morbidities were at the greatest risk as well as frequently having complex medication regimens [25] with subsequent negative health outcomes [26]. In another study conducted among 200 community-dwelling seniors, almost half of the participants had medication regimens that were complex; the common causes identified included misunderstanding of medication instructions and polypharmacy [27]. Polypharmacy has worsened over the last three decades with prescribed medication usage doubling to four times from 1988 to 2010 [28].…”
Section: Discussionsupporting
confidence: 86%
“…Finally, to avoid salami publication or duplicate publication, we did not include polypharmacy. We have previously published on polypharmacy using these data [27,47,48]. It is still an open question of by what degree polypharmacy explains medication complexity, and whether predictors of medication complexity differ between those with and without polypharmacy.…”
Section: Limitationsmentioning
confidence: 99%
“…Race does not differ on polypharmacy, similar to the study in ( Assari and Bazargan, 2019b ). Our study found consistent evidence of associations between polypharmacy and cognitive decline, but the association is lower than other studies ( Khezrian et al, 2019 ; Umegaki et al, 2019 ; Assari et al, 2020 ). Possible reasons include that there were only medication and morbidities assessed at a single time point ( Khezrian et al, 2019 ), cross-sectional study design, and use of only an individual cognitive test score or a single cognitive domain ( Umegaki et al, 2019 ).…”
Section: Discussionsupporting
confidence: 81%
“…In particular, previous work (Guthrie et al, 2010) showed that people with dementia are 17 times more likely to be prescribed an antipsychotic and twice as likely to be prescribed an antidepressant or a hypnotic/anxiolytic than older people without dementia. Some cross-sectional and longitudinal studies have suggested that polypharmacy is associated with cognitive decline and memory loss (Cheng et al, 2018;Khezrian et al, 2019;Soysal et al, 2019;Umegaki et al, 2019) and the same association was demonstrated among African American (AA) older adults (Assari et al, 2020). Previous research with cognitively unimpaired aged ≥70 years individuals also demonstrated that the risk of mild cognitive impairment (MCI) or AD was higher in individuals with multimorbidity, particularly in those with 4 + chronic conditions (Vassilaki et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…Although the rodent hippocampus and primate hippocampus differ in terms of their embryonic development, a cross-species comparison of anatomical connectivity provides evidence that the primate hippocampal long axis may be homologous to that of the rat ( Strange et al, 2014 ) (see Figure 1 ). In vivo ciHDE appears to be uniquely well-suited for determining the adverse effects associated with multiple drug combinations (i.e., polypharmacy) which can impair learning and memory function in vulnerable aging populations ( Assari et al, 2020 ). In vivo ciHDE also allows for an improved understanding of how systemically administered drugs differentially modulate neural network activity in healthy subjects and those with neurodegenerative diseases ( Robitsek et al, 2015 ; Ratner et al, 2021 ).…”
Section: Highlights and Conclusionmentioning
confidence: 99%